Factors determining need in improvement of quality of pre-competition training of shooters from rifle at the moving target - Ilyakhina, O. Yu.; Fadeev, A. S.; Bessonov, A. A.; Semonenko, M. S. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
Results of the researches of the authors on justification of the factors determining need in improvement of quality of the training of shooters from rifle at the moving target at pre-competitions period are presented in the article. These factors are: the high technical complexity of training of the shooters from rifle at the moving target; non-standard features in technique of performance of the well-aimed shot at the moving target; need in manifestation of synchronization of the skills of breath and aiming, and also choice of the means and methods of training at implementation of the program of the training. Important factors are: a set of grade levels and training of shooters from rifle at the moving target and also need in ensuring control over growth of the sports skill and the results in firing among the athletes. Keywords: factors, shooters from rifle at the moving target, skills of accurate shooting, improvement of quality of training.